The Role of γ-Tubulin in Centrosomal Microtubule Organization - O'Toole, Eileen; Greenan, Garrett; Lange, Karen I.; Srayko, Martin; Müller-Reichert, Thomas (PLOS ONE, 2012)
As part of a multi-subunit ring complex, γ-tubulin has been shown to promote microtubule nucleation both in vitro and in vivo, and the structural properties of the complex suggest that it also seals the minus ends of the polymers with a conical cap. Cells depleted of γ-tubulin, however, still display many microtubules that participate in mitotic spindle assembly, suggesting that γ-tubulin is not absolutely required for microtubule nucleation in vivo, and raising questions about the function of the minus end cap. Here, we assessed the role of γ-tubulin in centrosomal microtubule organisation using three-dimensional reconstructions of γ-tubulin-depleted C. elegans embryos. We found that microtubule minus-end capping and the PCM component SPD-5 are both essential for the proper placement of microtubules in the centrosome. Our results further suggest that γ-tubulin and SPD-5 limit microtubule polymerization within the centrosome core, and we propose a model for how abnormal microtubule organization at the centrosome could indirectly affect centriole structure and daughter centriole replication.